2017
DOI: 10.1097/igc.0000000000000961
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Endothelial Progenitor Cell Number in Early Stage of Endometrial Cancer

Abstract: These results strongly suggest new vessel formation from recruited endothelial precursors as being involved mainly at the early stages of tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
10
0
2
Order By: Relevance
“…Moreover, EPCs (including CECs) are increased in the peripheral blood of patients with various cancers, such as multiple myeloma [228], acute myeloid leukaemia [229, 230], nonsmall cell lung cancer (NSCLC) [231], hepatocellular carcinoma [232, 233], breast cancer [234–236], ovarian cancer [237], chronic lymphocytic leukaemia (CLL) [238], renal cell carcinoma (RCC) [239, 240], and endometrial cancer [241]. CECs have been implicated in tumour progression and aggressiveness [230, 231, 235, 237, 238, 240, 241]. Furthermore, in malignant breast carcinoma, EPCs are resistant to the cytokine TNF- α , which is responsible for inducing apoptosis [242].…”
Section: Current Prospectsmentioning
confidence: 99%
“…Moreover, EPCs (including CECs) are increased in the peripheral blood of patients with various cancers, such as multiple myeloma [228], acute myeloid leukaemia [229, 230], nonsmall cell lung cancer (NSCLC) [231], hepatocellular carcinoma [232, 233], breast cancer [234–236], ovarian cancer [237], chronic lymphocytic leukaemia (CLL) [238], renal cell carcinoma (RCC) [239, 240], and endometrial cancer [241]. CECs have been implicated in tumour progression and aggressiveness [230, 231, 235, 237, 238, 240, 241]. Furthermore, in malignant breast carcinoma, EPCs are resistant to the cytokine TNF- α , which is responsible for inducing apoptosis [242].…”
Section: Current Prospectsmentioning
confidence: 99%
“…Besides their role in cardiovascular diseases, circulating endothelial cells (CEC) are considered a biomarker for different neoplasms as they play a relevant role in tumour angiogenesis, which is essential for invasive tumour growth and metastasis [43]. Endothelial progenitor cell numbers (CD34, VEGFR2/KDR) in the peripheral blood of women with early endometrial carcinoma were significantly augmented compared with those of healthy control women, while circulating endothelial cell numbers (CD31, CD45) were similar in both groups [35]. By contrast, no prognostic significance or association with clinicopathological features have been demonstrated for the presence of disseminated tumour cells (DTC) in the bone marrow of endometrial carcinoma patients [44,45].…”
Section: Liquid Biopsy In Endometrial Cancermentioning
confidence: 99%
“…A comparison of anti‐CD34 and anti‐CD133 antibody‐coated stents found that the latter were more effective at capturing EPCs and achieved coating with an EPC layer in vitro . No significant difference in neointima formation and endothelialization was observed between the CD133 antibody‐coated stent and BMS in vivo , however, which may be due to the very low number of EPCs present in the circulatory system …”
Section: Introductionmentioning
confidence: 99%
“…13 No significant difference in neointima formation and endothelialization was observed between the CD133 antibody-coated stent and BMS in vivo, however, 14,15 which may be due to the very low number of EPCs present in the circulatory system. 16 Endothelialization of implanted stents can be achieved not only by circulating EPCs but also by ECs from the neighboring, intact endothelium and by circulating endothelial cells (cECs). We therefore targeted vascular endothelial growth factor receptor-2 (VEGFR2) for cell binding in this work as VEGFR2 is expressed on the surfaces of ECs, cECs, and EPCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation